ISLAM DAN KEARIFAN LOKAL: BELAJAR DARI KEARIFAN TRADISI MELAUT SUKU MANDAR - Idrus L.; Ridhwan Ridhwan (Didaktika : Jurnal Kependidikan, 2020)
This study aims to describe the local wisdom of the fishery tradition of Mandarese Tribe associated with Islamic value. Data was collected using interview and literature studies, then analyzed using a qualitative descriptive approach. The majority of the Mandarese people are Muslims who inhabit areas on the West coast of the Sulawesi Island. The primary profession of the Mandarese people is fishermen who have local wisdom in the form of belief in occult things at sea so that natural phenomena and supernatural powers become the driving force of spiritual energy. Some rituals need to be performed before and after sailing. This form of knowledge is known as the “paissangang posasiang” by the Mandarese people. Besides, some restrictions must not be violated (pemali). There is a combination of Islamic value and local wisdom within the Mandarese people, such as the belief in the figure of the Prophet Khidr, reading the Surah Yaasin when during a wind storm (laso anging), reading barzanji, praying for salvation based to Islamic value led by a kyai (annannguru).